Evaluation of Risk Scores as Predictive Tools for Stroke in Patients with Retinal Artery Occlusion: A Danish Nationwide Cohort Study - Ørskov, Marie; Vorum, Henrik; Larsen, Torben Bjerregaard; Skjøth, Flemming (TH Open, 2022)
Purpose We investigated the 1-year risk of stroke in patients with retinal artery occlusion and evaluated the predictive and discriminating abilities of contemporary risk stratification models for embolic stroke.Methods This register-based cohort study included 7,906 patients with retinal artery occlusion from Danish nationwide patient registries between 1995 and 2018. The study population was stratified according to the number of points obtained in the stroke risk scores: the CHA2DS2-VASc score and the ESSEN Stroke Risk score. The 1-year risk of stroke within strata was evaluated and compared using the cox proportional hazards model. Furthermore, the discrimination of the risk scores as predictive tools for stroke risk assessment was investigated using C-statistics, Brier score, and the index of prediction accuracy.Results The stroke event rate in patients with retinal artery occlusion increased as the score increased for both risk scores, ranging from 3.62 (95% confidence interval [CI]: 2.46–5.31) per 100 person-years to 13.25 (95% CI: 11.78––14.89) per 100-person-years for increasing levels of the CHA2DS2-VASc score and from 3.97 (95% CI: 2.97–5.32) per 100 person-years to 16.43 (95% CI: 14.01–19.27) per 100 person-years for increasing levels of the ESSEN Stroke Risk score. Using a risk score of 0 as a reference, the difference was statistically significant for retinal artery occlusion patients with a CHA2DS2-VASc score of 2 or above and for all levels of the ESSEN Stroke Risk score. The C-statistics for the risk scores was 61% (95% CI: 58%–63%) and 62% (95% CI: 59–64%) for the CHA2DS2-VASc score and ESSEN Stroke Risk score, respectively.Conclusion The results suggested that the use of the CHA2DS2-VASc score and the ESSEN Stroke Risk score was applicable for risk stratification of stroke in patients with retinal artery occlusion, but discrimination was poor due to low specificity.
Keywords: Retinal artery occlusion; Prediction; Risk scores; CHA2DS2-VASc score; ESSEN Stroke Risk score